Double-Edged Sword: Interleukin-2 Promotes T Regulatory Cell Differentiation but Also Expands Interleukin-13- and Interferon-γ-Producing CD8+ T Cells via STAT6-GATA-3 Axis in Systemic Lupus Erythematosus - Kato, Hiroshi; Perl, Andras (Frontiers in Immunology, 2021)
Interleukin-2 (IL-2) expands the depleted T regulatory (Treg) cell population, and it has emerged as a potential therapy in systemic lupus erythematosus (SLE). However, IL-2 administration may involve the risk of expanding unwanted pro-inflammatory cells. We herein studied the effects of IL-2 on pro-inflammatory cytokine production by CD4+ and CD8+ T cells in parallel with Treg development following CD3/CD28 co-stimulation. While Treg cells are depleted in SLE patients, their CD4+ T cells were poised to receive and activate IL-2 signaling as evidenced by upregulation of CD25 and enhanced IL-2-incued STAT5 phosphorylation during Treg differentiation. In patients with SLE, however, IL-2 also expanded CD8+ T cells capable of producing interleukin-5, interkeukin-13 (IL-13), and interferon-γ (IFN-γ) that occurred with enhanced expression of GATA-3 and phosphorylation of STAT6 but not STAT5. Our data pinpoint a safety signal for systemic administration of IL-2 and challenges a long-held conceptual platform of type 1 and 2 cytokine antagonism by newly documenting the IL-2-dependent development of IL-13 and IFN-γ double-positive (IL-13+IFNγ+) CD8+ T cells in SLE.